Advances and challenges in endoscopy training: A mixed methods study among endoscopy trainers in the Netherlands - Robert A Mousset; Agnes Diemers; Wouter H de Vos tot Nederveen Cappel; Jean-Pierre E.N. Pierie; Alexandra M.J. Langers; Paul L.P. Brand (Endoscopy International Open)
Background and study aims Variation between trainers in providing traditional gastrointestinal endoscopy training, in which residents learn endoscopy by doing under the supervision of endoscopy trainers, may cause differences in endoscopy competence between residents. In this study, we explored endoscopy trainers’ views on the current status and desired future best practices regarding endoscopy training.